Indian government endorses CGIAR Gender Researchers' Network: A credible resource for recommendations on agri-food systems research, policies, and investments - De Haan, Nicoline; Elias, Marlene (2024)
Global experts at the conference “From research to impact: Towards just and resilient agri-food systems” demonstrated that women’s empowerment and gender equality are crucial to sustainable and equitable agrifood system transformations. These insights followed the G20 Summit, where leaders committed to women-led development to enhance food security, nutrition, and climate action. The Indian President, Ministers, and G20 Sherpa inaugurated the conference and called for CGIAR recommendations on gender to inform their future agrifood systems’ improvements and G20 investments.